2008
DOI: 10.4049/jimmunol.181.9.6503
|View full text |Cite
|
Sign up to set email alerts
|

IL-4-Induced Selective Clearance of Oligomeric β-Amyloid Peptide1–42 by Rat Primary Type 2 Microglia

Abstract: A hallmark of immunopathology associated with Alzheimer’s disease is the presence of activated microglia (MG) surrounding senile plaque deposition of β-amyloid (Aβ) peptides. Aβ peptides are believed to be potent activators of MG, which leads to Alzheimer’s disease pathology, but the role of MG subtypes in Aβ clearance still remains unclear. In this study, we found that IL-4 treatment of rat primary-type 2 MG enhanced uptake and degradation of oligomeric Aβ1–42 (o-Aβ1–42). IL-4 treatment induced significant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 64 publications
4
91
0
Order By: Relevance
“…In support of this possibility, TNF␣ mRNA levels were selectively down-regulated in CX3CR1 deficient APPPS1 animals, and TNF␣ has been shown to directly reduce microglial expression of A␤-degrading enzymes such as insulin-degrading enzyme and neprilysin. 51,52 Furthermore, IL1␤ mRNA levels were significantly increased in a gene dose-dependent manner in the CX3CR1-deficient APPPS1 animals, and previous studies demonstrated that IL1␤ overexpression enhances A␤ clearance. 9,53 Finally, mRNA levels of MCP-1, which promotes microglia-mediated A␤ oligomerization, 54 was reduced in CX3CR1-deficient APPPS1 animals and thus could lead to reduced A␤ oligomerization/ deposition.…”
Section: Microglial Removal Of A␤mentioning
confidence: 79%
See 1 more Smart Citation
“…In support of this possibility, TNF␣ mRNA levels were selectively down-regulated in CX3CR1 deficient APPPS1 animals, and TNF␣ has been shown to directly reduce microglial expression of A␤-degrading enzymes such as insulin-degrading enzyme and neprilysin. 51,52 Furthermore, IL1␤ mRNA levels were significantly increased in a gene dose-dependent manner in the CX3CR1-deficient APPPS1 animals, and previous studies demonstrated that IL1␤ overexpression enhances A␤ clearance. 9,53 Finally, mRNA levels of MCP-1, which promotes microglia-mediated A␤ oligomerization, 54 was reduced in CX3CR1-deficient APPPS1 animals and thus could lead to reduced A␤ oligomerization/ deposition.…”
Section: Microglial Removal Of A␤mentioning
confidence: 79%
“…48 Within the AD brain, there is a chronic activation of microglia associated with inflammatory cytokines including TNF␣ that can substantially block of ability of the microglia to remove 47,49,50 or degrade A␤. 51,52 Recent studies demonstrated that overexpression of IL1␤, an inflammatory cytokine leads to reduced A␤ pathology in mouse models of AD. 9,53 One partial explanation for our results is that CX3CR1 deficiency alters the microglial activation status and enhances A␤ clearance.…”
Section: Microglial Removal Of A␤mentioning
confidence: 99%
“…In AD mouse models, the expression levels of neprilysin and IDE in microglia were decreased in 14-month-old mice (Hickman et al, 2008). Recent studies demonstrated that IDE expression and activity were complexly regulated by various factors, including aging, Apo E, cytokines, and vitamin E (Eckman and Eckman, 2005;Jiang et al, 2008;Shimizu et al, 2008;Nishida et al, 2009). Therefore, the upregulation of IDE represents a promising strategy for therapy and prevention for AD.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that peripheral mononuclear cells from AD patients showed reduced IL-4 production upon stimulation [107]. In vitro, IL-4 induces the microglial clearance of Ab via promoting the expression of CD36 and Ab-degrading enzymes (neprilysin and insulin-degrading enzyme) [108]. Moreover, in vivo treatment with IL-4 reduces the accumulation of Ab and alleviates the cognitive impairments in AD animal models [109].…”
Section: Il-4mentioning
confidence: 96%